2015
DOI: 10.1016/j.neuroimage.2014.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Early visual cortex reflects initiation and maintenance of task set

Abstract: The human brain is able to process information flexibly, depending on a person's task. The mechanisms underlying this ability to initiate and maintain a task set are not well understood, but they are important for understanding the flexibility of human behavior and developing therapies for disorders involving attention. Here we investigate the differential roles of early visual cortical areas in initiating and maintaining a task set. Using functional Magnetic Resonance Imaging (fMRI), we characterized three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Sustained signals from the cingulo-opercular network are related to the maintenance of task sets (Dosenbach et al 2008; Nelson et al, 2010), though their precise function remains unclear (Dubis et al 2014). Recent work by our lab has demonstrated that sustained task-driven responses occur in early visual areas including V1 (Elkhetali et al 2015), but do not show the spatial specificity of cue-driven and stimulus-driven responses (Griffis et al 2015b). While we have interpreted these sustained V1 responses as reflecting ongoing task maintenance signals that are likely to have originated in the cingulo-opercular network, it is unclear why this network would show preferential connectivity to the near-periphery of V1 during fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sustained signals from the cingulo-opercular network are related to the maintenance of task sets (Dosenbach et al 2008; Nelson et al, 2010), though their precise function remains unclear (Dubis et al 2014). Recent work by our lab has demonstrated that sustained task-driven responses occur in early visual areas including V1 (Elkhetali et al 2015), but do not show the spatial specificity of cue-driven and stimulus-driven responses (Griffis et al 2015b). While we have interpreted these sustained V1 responses as reflecting ongoing task maintenance signals that are likely to have originated in the cingulo-opercular network, it is unclear why this network would show preferential connectivity to the near-periphery of V1 during fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Task and stimulus details have been described in detail elsewhere (Elkhetali et al 2015; Griffis et al 2015b), and will only be briefly described here, as current analyses focus on the rest periods only. Task blocks consisted of unimodal and bimodal visual and auditory attention tasks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, participants performed discrimination tasks on unimodal stimuli (visual or auditory) or bimodal stimuli (intermodal attention to only the visual or auditory portion of simultaneously presented visual and auditory stimuli). We found that trial-driven activity in V1 depended on presented stimuli, while activity related to the initiation and maintenance of task sets depended instead on the attended modality of the task regardless of presence or absence of intermodal distractors (Elkhetali et al, 2015). This suggests that even at the level of primary visual cortex, task-appropriate visual processing may be accomplished by the joint action of temporally distinct top-down control processes that differ in their stimulus-dependence vs. task-dependence.…”
Section: Introductionmentioning
confidence: 92%
“…In our previous study, we observed that trial-driven and task-set related responses in V1 varied in different ways depending on a participant’s task (Elkhetali et al, 2015). Task set-related activity in V1 was greater during visual attention than auditory attention for a task with simultaneous visual and auditory stimuli, whereas this was not true for trial-driven activity.…”
Section: Introductionmentioning
confidence: 99%